Hallux interphalangeal involvement after metatarsophalangeal joint arthrodesis. Treatment and Results - Enzo Sperone; Martín Rofrano; Andrés Bigatti; Matías Iglesias; Iván Torterola; Alberto Macklin Vadell (Journal of the Foot & Ankle, 2020)
Objective: To assess the involvement of the hallux interphalangeal (IP) joint after first metatarsophalangeal joint (MTPJ) arthrodesis and propose a treatment consisting of MTPJ resection arthroplasty associated with phalangeal osteotomy or IP joint arthrodesis. Methods: We retrospectively analyzed 9 patients treated with MTPJ resection arthroplasty associated with phalangeal osteotomy or hallux IP joint arthrodesis from November 2006 to January 2017. Results: The main causes of MTPJ arthrodesis that subsequently evolved to IP involvement were severe hallux valgus and sequelae or complications of previous hallux valgus operations. Additionally, the reasons leading to rescue surgery were pain, deformity, and/or discomfort. Conclusion: This therapeutic modality is able to relieve symptoms by a simple procedure, with acceptable functional and esthetic results. Level of Evidence IV; Therapeutic Studies; Case Series.